A core syllabus for the teaching of gross anatomy of the thorax to medical students. Issue 2 (12th December 2019) - Moxham, Bernard J.; Stephens, Shiby; Sharma, Deepak; Loukas, Marios
Abstract : Discussion is ongoing concerning the need to ensure the clinical relevance of the biomedical sciences. However, clinical relevance within health care courses presupposes that there is internationally agreed core material to be taught and learned. For anatomy, by the initial use of Delphi Panels that comprise anatomists, scientists, and clinicians, the International Federation of Associations of Anatomists (IFAAs) is developing internationally accepted core syllabuses for all anatomical sciences disciplines in the health care professions. In this article, the deliberations of a Delphi Panel for the teaching of thoracic anatomy in the medical curriculum are presented, prior to their publication on the IFAA's website. To develop the syllabus further, it is required that anatomical societies, as well as individual anatomists and clinicians, comment upon, elaborate, and amend this draft recommended syllabus. The aim is to set internationally recognized standards and thus to provide guidelines concerning the knowledge of the human thorax expected of graduating medical professionals. Such information should be borne in mind by those involved in the development of medical courses. Clin. Anat. 33:300–315, 2020. © 2019 Wiley Periodicals, Inc.